Patient information portal for congenital aortic and pulmonary valve disease: a stepped-wedge cluster randomised trial - Etnel, Jonathan R G (Open Heart, 2021)
BACKGROUND: In response to an increased need for patient information in congenital heart disease, we previously developed an online, evidence-based information portal for patients with congenital aortic and pulmonary valve disease. To assess its effectiveness, a stepped-wedge cluster randomised trial was conducted. METHODS: Adult patients and caregivers of paediatric patients with congenital aortic and/or pulmonary valve disease and/or tetralogy of Fallot who visited the outpatient clinic at any of the four participating centres in the Netherlands between 1 March 2016–1 July 2017 were prospectively included. The intervention (information portal) was introduced in the outpatient clinic according to a stepped-wedge randomised design. One month after outpatient clinic visit, each participant completed a questionnaire on disease-specific knowledge, anxiety, depression, mental quality of life, involvement and opinion/attitude concerning patient information and involvement. RESULTS: 343 participants were included (221 control, 122 intervention). Cardiac diagnosis (p=0.873), educational level (p=0.153) and sex (p=0.603) were comparable between the two groups. All outcomes were comparable between groups in the intention-to-treat analyses. However, only 51.6% of subjects in the intervention group (n=63) reported actually visiting the portal. Among these subjects (as-treated), disease-specific knowledge (p=0.041) and mental health (p=0.039) were significantly better than in control subjects, while other baseline and outcome variables were comparable. CONCLUSION: Even after being invited by their cardiologists, only half of the participants actually visited the information portal. Only in those participants that actually visited the portal, knowledge of disease and mental health were significantly better. This underlines the importance of effective implementation of online evidence-based patient information portals in clinical practice.